Measuring efficiency from casemix funding in Victoria using the stochastic frontier - Mangano, Maria (Centre for Research in Applied Economics, Curtin Business School, Curtin University of Technology, 2007)
The Australian state of Victoria experienced a fundamental change in public hospital funding in 1993 with the introduction of casemix funding using diagnosis related groups. One of the primary drivers of this altered funding regime was to introduce a mechanism by which public hospitals could be compared for costs. Cost comparisons would then create an incentive for efficiency improvements because efficient hospitals would attract increased funding. This paper applies stochastic frontier estimation of a production function to panel data for the period 92/93 to 95/96 in order to establish whether, in fact, efficiency improvements were realised over this period. The results show that there was no significant change to individual hospital efficiency levels.